Survival of patients with metastatic leiomyosarcoma: the MD Anderson Clinical Center for targeted therapy experience. (23rd November 2016) - Wang, Zhijie; Shi, Naiyi; Naing, Aung; Janku, Filip; Subbiah, Vivek; Araujo, Dejka M.; Patel, Shreyaskumar R.; Ludwig, Joseph A.; Ramondetta, Lois M.; Levenback, Charles F.; Ramirez, Pedro T.; Piha‐Paul, Sarina A.; et al.
Abstract: Advanced stage leiomyosarcoma (LMS) is incurable with current systemic antitumor therapies. Therefore, there is clinical interest in exploring novel therapeutic regimens to treat LMS. We reviewed the medical records of 75 consecutive patients with histologically confirmed metastatic LMS, who had been referred to the Clinical Center for Targeted Therapy at MD Anderson Cancer Center. To lay the foundation for potential phase I trials for the treatment of advanced LMS, we analyzed tumor response and survival outcome data. The frequent hotspot gene aberrations that we observed were the TP53 mutation (65%) and RB1 loss/mutation (45%) detected by Sequenom or next‐generation sequencing. Among patients treated with gene aberration‐related phase I trial therapy, the median progression‐free survival was 5.8 months and the median overall survival was 15.9 months, significantly better than in patients without therapy (1.9 months, P = 0.001; and 8.7 months, P = 0.013, respectively). Independent risk factors that predicted shorter overall survival included hemoglobin <10 g/dL, body mass index <30 kg/m 2, serum albumin <3.5 g/dL, and neutrophil above upper limit of normal. The median survivals were 19.9, 7.6, and 0.9 months for patients with 0, 1 or 2, and ≥3 of the above risk factors, respectively ( P < 0.001). A prognostic scoring system that included four independent risk factors might predict survival in patients with metastatic LMS who were treated in a phase I trial. Gene aberration‐related therapies led to significantly better clinical benefits, supporting that further exploration with novel mechanism‐driven therapeutic regimens is warranted. Abstract : In patients with metastatic leiomyosarcoma who were referred to a phase I trial service, we observed TP53 and Rb hotspot mutations in a majority of patients. Gene aberration‐related phase I trial therapies provided survival benefit. Efforts should be made to delineate biological and molecular characteristics of leiomyosarcoma to facilitate future drug development.